Synthesis and evaluation of the antioxidant activity of new spiro-1,2,4-triazine derivatives applying Ag/Fe3O4/CdO@MWCNT MNCs as efficient organometallic nanocatalysts - Ezzatzadeh, Elham; Soleimani-Amiri, Somayeh; Hossaini, Zinatossadat; Khandan Barani, Khatereh (Frontiers in Chemistry, 2022)
We applied the Petasites hybridus rhizome water extract as green media so that the Ag/Fe3O4/CdO@ Multi-Walled Carbon Nanotubes magnetic nanocomposits (Ag/Fe3O4/CdO@MWCNTs MNCs) could be prepared. We also evaluated its activity by using in the one-pot multicomponent reaction of acetophenones, diethyloxalate, ammonium acetate, activated carbonyl compounds such as ninhydrin, isatin and acenaphthylene-1,2-dione, malononitrile and hydrazoyl chlorides in aqueous medium at room temperature for the generation of spiro-1,2,4-triazines as new derivatives with tremendous output. Besides, reducing organic pollutants of the 4-nitrophenol (4-NP) was carried out by generating Ag/Fe3O4/CdO@MWCNTs in water at room temperature. The results displayed the Ag/Fe3O4/CdO@MWCNTs reduced pollutants of organic compounds in a short time. The synthesized spiro-1,2,4-triazines have NH and OH functional groups having acidic hydrogen with high antioxidant power. Also, the spiro-1,2,4-triazines exhibited antimicrobial ability. For this purpose, the disk diffusion method was applied and two kinds of bacteria Gram-positive and Gram-negative were employed for the analysis. Further, we applied functional theory-based quantum chemical methods in order that we would better understand reaction mechanism density. To generate spiro-1,2,4-triazines, the applied process showed many properties such as reactions with short time, product with good yields, simple extraction of catalyst from mixture of reaction.